Differential assessment of frontally-mediated behaviors between self- and informant-report in patients with obsessive-compulsive disorder following gamma ventral capsulotomy. (6th June 2022) - Kassel, Michelle T.; Lositsky, Olga; Vaidya, Avinash R.; Badre, David; Malloy, Paul F.; Greenberg, Benjamin D.; Marsland, Richard; Noren, Georg; Sherman, Anna; Rasmussen, Steven A.; McLaughlin, Nicole C.R.
Abstract: Obsessive-Compulsive Disorder (OCD) is a debilitating disorder causing marked distress and functional impairment. While advances in behavioral and pharmacotherapies have been effective for a majority of patients with OCD, 10–30% remain treatment refractory and severely impaired. For a subset of treatment-resistant individuals with the most severe and disabling (intractable) illness, gamma ventral capsulotomy (GVC) appears effective in reducing OCD symptoms and functional impairment. However, the effects of the ventral internal capsule lesion via GVC surgery on executive function in everyday life have been minimally investigated. Examining behavioral outcomes of GVC also provides a rare opportunity to probe the functional importance of the ventral prefrontal-subcortical connections of the internal capsule white matter tract in a relatively homogenous sample of patients with comparable white matter lesions. The present study investigated changes in frontally-mediated behaviors, measured by the Frontal Systems Behavior Scale (FrSBe), following GVC in 45 individuals with severe and otherwise intractable OCD, as rated by patients themselves and family members. Linear mixed effects models revealed a significant improvement in patient self-ratings on the FrSBe after surgery, while family ratings did not significantly change. Interestingly, improvement on the FrSBe for both self and family raters was significantly correlated with improvement in OCD symptomatology post-surgery, as measured by the Yale-Brown Obsessive Compulsive Scale (Y-BOCS). At the group level, we found no evidence of decline in frontally-mediated behaviors assessed by the FrSBe as a result of focal white matter disconnection via GVC. However, we cannot rule out the possibility that placebo effects or compromised patient self-awareness or insight contributed to the significant improvement in self ratings. Our measures may also have limited sensitivity to more selective impairments that could result from a small lesion to the ventral internal capsule. The present study demonstrates the need for detailed investigation of cognitive and behavioral changes as important factors when considering GVC as a viable treatment option for patients with refractory OCD. Highlights: Ventral capsulotomy is a treatment for intractable obsessive-compulsive disorder Impact of gamma ventral capsulotomy on frontal behaviors remains unclear No significant declines in frontal lobe functioning were found post-surgery Self but not informant reports of frontal behaviors improved post-surgery Assessment of metacognition after ventral capsulotomy may be beneficial